The impact of the entrepreneur and firm related factors on small and medium enterprise sales growth - Ajtene Avdullahi; Vjosa Fejza Ademi (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2020)
Purpose: In nowadays economy, the role of Small and Medium Enterprises (SMEs) is continually increasing as they represent the primary source of employment, economic development, poverty alleviation, new product development, and innovations. The SMEs' growth depends mostly upon its internal factors like the entrepreneur related factors and firm related factors. The main objective of this research is to explore how these internal factors influence SMEs' sales growth. Design/methodology/approach: For our research purpose, we have used a sample of 600 business owners of SMEs across Kosovo, and the multivariate regression analysis is developed to test the four hypotheses that we have set. Findings: In our research, we did not find any significant statistical relation for the positive effect of the entrepreneur's education on SMEs' sales growth. We found negative support to our hypothesis: Female Entrepreneurs will be positively related to SMEs' sales growth. Our research results indicate that variable Business age have an impact on the firm's sales, whereas, regarding the firm size, our results indicate that the bigger is the number of employees within a firm, the firm will experience the higher sales growth. Research implications: Based on our research results, we suggest that entrepreneurs should attend long-term and high quality training considering their positive effects on the firms' growth, whereas female entrepreneurs and managers should improve their management and business skills, cash flow and, technical skills and create sustainable networks. Originality/value: This paper will contribute to existing theory by filling the gap in the literature on the impact of the entrepreneur and firm related factors on small and medium enterprise growth with empirical evidence from a unique transitional country.
Keywords: L25; L26; 330; Entrepreneur's education; entrepreneurs' gender; firms' age; firms' size; SMEs' sales growth